'All you that be young, whom I do now represent': Doctrine, Deception and Discontent in Lusty Juventus. Issue 3 (15th April 2020) - Caputo, Nicoletta
Abstract: In a period when harsh controversy was dominant, the Edwardian interlude Lusty Juventus is remarkable for presenting a different aspect of Reformation propaganda that eschewed vituperative anti‐Catholicism and aimed rather at creating a doctrinal consensus around the key tenets of the New Creed. At the same time, however, anxiety for the moral situation of the Edwardian Church can be discerned in the play. With its doctrinal emphasis, its conciliatory stance and its incipient discontent, this quite‐neglected interlude stands out as a fundamental step in the development of the drama connected to the Tudor Reformation. Such theatrical production began with the polemical anti‐Catholicism of John Bale's plays, which fed on vituperation and verbal abuse, and culminated in the Elizabethan so‐called money plays, which castigated contemporary social and religious evils alike, and bitterly deplored the failure of the Reformation to bring about that utter moral regeneration its champions so fervently advocated.